PULMONARY HYPERTENSION IN PATIENTS WITH IDIOPATHIC PULMONARY FIBROSIS BY USING ECHO CARDIOGRAPHY - Muhammad Hanif1 , Naveed Ahmed Brohi2 , Safdar Ali Jamali3 , Muhammad Azhar4 , Mir Tahir Hussain Talpur5 , Mukhtyar Ahmed Abro6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2022)
ABSTRACT INTRODUCTION: Pulmonary hypertension has been linked to significantly worse outcomes in patients with idiopathic pulmonary fibrosis, who frequently experience confusion in their treatment. Idiopathic pulmonary fibrosis is a type of undiagnosed, progressive, chronic, fibrosing interstitial pneumonia that primarily affects older people. Right heart failure, reduced exercise capacity, and death are the outcomes of pulmonary hypertension, a group of destructive diseases. OBJECTIVE: Using a non-invasive technique called echocardiography, This study sought to determine the prevalence of pulmonary hypertension in idiopathic pulmonary fibrosis patients. METHODOLOGY: This descriptive cross-sectional study was conducted at the Jinnah Postgraduate Medical Center in Karachi's department of chest medicine, among 96 patients of aged 50-70 years. Patients with idiopathic pulmonary fibrosis of either gender were included. Patients were selected through non-probability purposive sampling. All the included patients were assessed for pulmonary hypertension echo cardiography under the supervision of consultant having > 5 years of experience. All the collected information was entered into the predesigned proforma. RESULTS: Mean age and duration of pulmonary hypertension were 62.36±6.16 years and 3.94±0.49 months respectively. Majority of the patients were female. The frequency of Pulmonary hypertension was found to be 38 (40%) in patients with idiopathic pulmonary fibrosis. CONCLUSION It is concluded that frequency of pulmonary hypertension is moderate. Evaluation of the presence of PH in patients with IPF may be helpful in determining the progression and prognosis of the disease. Echocardiography is non-invasive and less expensive method to detect pulmonary hypertension.